Ethnopharmacological survey of home remedies used for treatment of hair and scalp and their methods of preparation in the West Bank-Palestine - Abdel Naser Zaid; Nidal Amin Jaradat; Ahmad Mustafa Eid; Hamzeh Al Zabadi; Abdulsalam Alkaiyat; Saja Adam Darwish (BMC, 2017)
Abstract Background Natural products have many uses and purposes, including those linked to pharmaceutics and cosmetics. The aim of this study was to investigate the use of natural remedies for the treatment of hair and scalp disorders in the West Bank, Palestine. Methods An ethnopharmacological survey of herbal remedies and other natural products used in cosmetics and cosmeceuticals was carried out in the West Bank, Palestine. A questionnaire was distributed to 267 herbalists, traditional healers, hairdressers and rural dwellers. Collected information included: the names of plants and other natural products, the parts used, hair conditions, diseases and problems for which these products were used and also their methods of preparation. To identify the most important species used, the factor of informant's consensus (Fic), fidelity level (Fl) and the use-value (UV) were calculated. Results Collected data showed that 41 plants are utilized for the treatment of hair and scalp disorders, belonging to 27 families; among them Lamiaceae and Rosaceae, which were the most commonly used. Plant oils and their fruits are the most commonly used parts. Hair loss, dandruff, split hair endings and lice treatment, are reported as the most treated disorders. The number of plant species used consisted of 19, 14, 13, and again 13 with a factor of informant's consensus (Fic) for these disorders corresponding to 0.93, 0.94, 0.95 and 0.92, respectively. Fl was 100% for many plants; the highest UV value (0.84) was registered for Lawsonia inermis, which belongs to the Lythraceae family. Conclusions This study showed that many natural remedies are still used in Palestine for the treatment of scalp and hair disorders as well as for cosmeceutical purposes. This study is of great importance as it allows us to have a greater perspective on our folkloric use of these natural products. A combined scientific effort between informants and the scientific community, working in this field, may help in the discovery of new cosmetics, cosmeceutical and nutraceutical products.